2014
DOI: 10.1089/mab.2014.0001
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of a Monoclonal Antibody Against GRAM Domain-Containing Protein 1A

Abstract: From the proteomic analysis, we identified hundreds of novel proteins that have never been characterized for their expression profile and function on human embryonic stem (hES) cells. In this study, we produced a group of monoclonal antibodies against the GRAM domain-containing protein 1A, which was found on hES cells. Using these antibodies, we analyzed the expression of GRAMD1A in various tissues and tumor cell lines. The results showed that GRAMD1A is expressed in the nucleus and cytoplasm of hES cells, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…GRAMD1A is widely expressed in the nucleus and cytoplasm of embryonic stem cells, cancer cell lines, and ectodermal, mesodermal, and endodermal tissues, and its function has not been fully explored [ 8 ]. In previous studies, GRAMD1A was found to accumulate at autophagosome initiation sites, influence cholesterol distribution during starvation, and participate in autophagosome biogenesis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRAMD1A is widely expressed in the nucleus and cytoplasm of embryonic stem cells, cancer cell lines, and ectodermal, mesodermal, and endodermal tissues, and its function has not been fully explored [ 8 ]. In previous studies, GRAMD1A was found to accumulate at autophagosome initiation sites, influence cholesterol distribution during starvation, and participate in autophagosome biogenesis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…GRAM domain-containing protein 1A (GRAMD1A), originally identified in human embryonic stem cells, is 724 amino acids in length and contains a GRAM structural domain [ 8 ]; it is thought to be an intracellular protein-binding or lipid-binding signalling domain and may play an important role in membrane-associated processes [ 9 ]. GRAMD1A is found to be expressed in a variety of human cancer tissues, including the digestive, urinary, and reproductive systems [ 8 ]. In addition, GRAMD1A was found to promote the expansion of hepatocellular carcinoma stem cells, the growth of hepatocellular carcinoma, and resistance to chemotherapy via STAT5 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The class and subclass of the isotypes of the purified antibody were determined by using a mouse monoclonal antibody isotyping kit. Measurement of monoclonal antibody affinity (Ka) was carried out according to the procedure described by Jiang et al [5] . An indirect competitive ELISA (icELISA) standard curve was developed based on the mAbs.…”
Section: Characterization Of Monoclonal Antibodiesmentioning
confidence: 99%
“…IL-6/Jak2/Stat3 pathway promotes HCC growth, chemoresistance and the self-renewal of HCC stem cells91011. GRAMD1A first finds in human embryonic stem cell, and expresses in ectoderm, mesoderm and endoderm tissues and many tumor cells12, its function hasn’t been explored. Here, we studied the role of GRAMD1A in the prognosis, initiation and progression of HCC, we analyzed the correlation between GRAMD1A levels and many clinicopathological features, and examined whether GRAMD1A could function as a prognostic factor for HCC patients.…”
mentioning
confidence: 99%